Antimalarial Potential of Ostruthin Isolated from Luvunga sarmentosa Root and Stem: In Vitro and In Silico Studies - Ahmad, Waqar; Wicaksana, Firman; Ilmi, Hilkatul; Tumewu, Lidya; Faturrahman, Muhammad; Winarko, Peggy Ignatia; Rakhmawati, Cindi Dia; Suciati, Suciati; Hafid, Achmad Fuad; Widyawaruyanti, Aty (Trends in Sciences, 2024)
The high morbidity and mortality due to malaria infection worldwide led to the demand for new antimalarial drug development, one of which is utilizing herbal medicines as a new alternative to malaria treatment. This study aims to isolate and identify antimalarial compounds from Luvunga sarmentosa root and stem by bioassay-guided isolation approach. Luvunga sarmentosa root and stem were extracted, fractionated and purified to obtain an antimalarial compound. Compound identification was conducted based on 1H, 13C and 2D NMR. The LDH assay was used to test the antimalarial activity against Plasmodium falciparum. A molecular docking study was performed on PfDHODH (PD-ID: 1TV5) and PfLDH (PD-ID: 1LDG) using Autodock tools. The bioassay-guided isolation obtained a coumarin compound identified as ostruthin (6-geranyl-7-hydroxycoumarin) as antimalarial isolated from L. sarmentosa root and stem extract. Ostruthin exhibited antimalarial activity with an IC50 value of 2.65 ± 0.07 µg/mL against P. falciparum. The molecular docking results showed that ostruthin was predicted as a potential PfDHODH and PfLDH inhibitor based on their binding affinity which are −9.94 ± 0.11 and −8.84 ± 0.11 kcal/mol, respectively, and their interaction with receptor’s amino acids. Ostruthin isolated from the root and stem of L. sarmentosa is active as an antimalarial, and further research, such as in vivo studies and clinical trials, is needed to develop this compound as a drug. HIGHLIGHTS Luvunga sarmentosa is a traditional medicine used by the Dayak tribe to treat aphrodisiacs and fever Isolation of active compound from Luvunga sarmentosa root and stem was conducted by bioassay-guided isolation approach The antimalarial studies suggest that dichloromethane extracts of Luvunga sarmentosa root and leaves have a more potent antimalarial than hexane and methanol extract Ostruthin (6-geranyl-7-hydroxycoumarin) was successfully isolated from the roots and stems of Luvunga sarmentosa Ostruthin inhibited P. falciparum in vitro and potentially inhibited PfDHODH and PfLDH based on in silico studies GRAPHICAL ABSTRACT